THE EFFECT OF FINANCIAL DISTRESS, ESG DISCLOSURE, SALES GROWTH, AND PROFITABILITY ON TAX AVOIDANCE - Wahyu Anita, Amalia; Imarotus Suaida; Fitria Magdalena S. (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2026)
This study aims to examine the relationship between tax avoidance and several factors, including financial distress, environmental, social, and governance (ESG) disclosure, sales growth, and profitability, in raw material and energy manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2024. This research employs quantitative methods and utilizes secondary data obtained from financial and sustainability reports. Sixteen companies were selected through purposive sampling. The results show that financial difficulties positively affect tax avoidance, whereas profitability negatively affects it. Tax avoidance is not significantly impacted by sales growth or ESG disclosure. But then, when analyzed simultaneously, financial distress, ESG disclosure, sales growth, and profitability all contribute to shaping corporate tax avoidance practices. These findings suggest that companies facing financial pressure or demonstrating high profitability may be more inclined to avoid taxes. On the other hand, sales growth and ESG transparency appear to have limited impact, indicating that ESG initiatives do not automatically prevent such practices. Overall, this study broadens our understanding of corporate tax avoidance and informs governments in formulating more effective policies to curb it, such as risk-based monitoring systems.